Avaliação do uso preemptivo e preventivo da coadministração de fármacos em cirurgias de remoção de terceiros molares: revisão de escopo, revisão sistemática e ensaio clínico randomizado - Cetira Filho, Edson Luiz (2023)
Preoperative analgesic strategies have been alternatives for the management of inflammatory events in third molar (3M) removal surgery. The objective was to evaluate: 1) methodological quality of Randomized Clinical Trials (RCTs) related to lower 3M surgery; 2) evidence from primary studies investigating the efficacy of preemptive pharmacological coadministration in inflammatory events resulting from surgical removal of 3M; 3) evaluation of clinical outcomes related to surgical removal of lower 3M under different preemptive analgesia strategies. In Chapter 1, scoping review was performed on adherence to the 3M Removal RCT CONSORT guide. Twenty-nine studies were included. An inverse correlation was observed between the year of publication and the number of citations in Scopus, time between acceptance and publication and time between study completion and publication. Adherence to the CONSORT guide proved necessary to mitigate methodological errors and possible biases in RCTs involving 3M. In chapter 2, a systematic review was carried out according to the PRISMA guide. A synthesis without meta-analysis included 9 studies (484 patients). Preemptive drug coadministration (PDC) has primarily involved corticosteroids (Cort) and nonsteroidal anti-inflammatory drugs (NSAIDs). PDC involving Cort and other medications reduced pain scores (6 and 12h) and edema (48h). PDC from NSAIDs and other medications reduced pain scores (6, 8 and 24h), while edema and trismus improved after 48h. PDC may provide benefit in reducing the severity of inflammatory outcomes related to lower 3M surgery. In chapter 3, a triple-blind, split-mouth RCT was carried out with 48 volunteers who required bilateral removal of lower 3M, following a bifactorial design. The first factor of the study was the drug used, which included ibuprofen-arginine 770mg (Ib-Ar) co-administered with dexamethasone 8mg (DX) or ibuprofen-arginine 770mg placebo (P-Ib-Ar) co-administered with a dexamethasone placebo 8mg (P-DX). The second factor was the moment of administration of these medications (1 hour before the surgical procedure or immediate postoperative period), with four groups. The following were evaluated: pain scores, rescue medication, facial edema, maximum mouth opening, neutrophil measurement, impact on quality of life, perception of pain catastrophizing (PPC) and sleep quality (PSQI). The pain peak occurred after 2h (P-Ib-Ar group), while the other groups showed a pain peak after 4h. The total amount of rescue medication consumed was significantly lower in the groups treated with Ib-Ar + P-DX and Ib-Ar + DX compared to the groups treated with P-Ib-Ar. As for edema, in the groups treated with P-Ib-Ar and P-DX the measurements increased significantly and the group treated with DX returned to baseline values after 7 days. The measurement of neutrophils was attenuated in the groups using drugs alone or in combination. Mouth opening amplitude, OHIP-14 domains and mean PPC scores did not 11 differ between groups. The PSQI scores were higher in the P-Ib-Ar + P-DX group after 24h and in the P-Ib-Ar + P-DX and P-Ib-Ar + DX groups after 7d. The benefit of co-administration of both strategies was greater than the isolated use of the drugs.